IMPLEMENTASI SURAT EDARAN DIRJEN BIMAS No. P-005/ DJ. III/HK.00.7/10/2021 TENTANG IDDAH SUAMI (Studi Pada Kantor Urusan Agama di Kota Bandar Lampung) - Teresa, Teresa; Firdawati, Linda; Zaelani, Abdul Qodir (Al-Maslahah : Jurnal Ilmu Syariah, 2024)
This study aims to determine whether the implementation of Circular Letter of the Director General of Bimas No. P-005/ DJ. III/HK.00.7/10/2021 concerning husband's iddah (Study at the Office of Religious Affairs in Bandar Lampung City) is effective. In addition to seeing the purpose of Director General of Religious Affairs Circular No. P-005/DG. III/HK.00.7/10/2021 in mubādalah. Problems regarding marriage are basically cases that continue to grow and become more complex. One of them is about the breakup of marriage which results in the implementation of iddah, whether iddah due to divorce or death. From several definitions put forward, the essence of iddah can be compiled, namely the period that must be waited for by a woman who has divorced from her husband so that she can remarry to find out whether her womb is clean or to carry out Allah's orders. Departing from the literature written by Religious Court judges, if a husband or man divorces his wife in the context of divorce raj'i then while the wife's iddah period is still ongoing the husband or man enters into a new marriage with another woman without the knowledge of the wife and family, then returns to refer to his wife before the wife's iddah period is over, this will certainly lead to legal fraud, namely illegal polygamy. This study uses descriptive analytical qualitative research. The form of implementation of the KUA in Bandar Lampung City regarding this circular letter is the prohibition to marry a husband whose wife's iddah period has not been completed in order to prevent polygamy in disguise to provide legal certainty, provide legal order and provide clarity to men who marry during the iddah period of a wife who is divorced raj'i. Speaking of male iddah in the concept of mubādalah, the concept of intermarriage itself does not aim to dominate one party and is not only about the relationship between two parties related to the spirit of partnership, cooperation, reciprocity, general or special relations.